HUBUNGAN STIGMA KELUARGA TERHADAP TINGKAT KEPATUHAN PENGOBATAN PADA PASIEN GANGGUAN JIWA DI PUSKESMAS LANGSA BARAT - Cut Lianda Faradila; Ajma’in; Husaini (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Mental disorders are a global health issue with widespread impacts, not only on individuals affected but also on their families and society. One of the factors influencing the success of mental disorder treatment is the level of stigma experienced by the patient's family. This stigma can affect the family's support for the patient's adherence to treatment. Objective: General Objective: To determine the relationship between family stigma and medication adherence among patients with mental disorders at Langsa Barat Public Health Center. Specific Objectives: To examine the relationship between family stigma and the level of medication adherence in patients with mental disorders at Langsa Barat Public Health Center. Methods: This study used a quantitative method with a descriptive correlational design and a cross-sectional approach. The sample consisted of 60 families of mental disorder patients selected using purposive sampling. Data were collected through the Family Stigma Questionnaire and the Morisky Medication Adherence Scale (MMAS-8) and analyzed using the chi-square test. Results: The study found that the majority of families experienced a moderate level of stigma (85%). Meanwhile, patient treatment adherence was categorized as high (33.3%), moderate (48.3%), and low (18.3%). Statistical analysis showed no significant relationship between family stigma and treatment adherence in mental disorder patients (p-value = 0.07 > 0.05). Conclusion: The majority of families of patients with mental disorders at the Langsa Barat Community Health Center experience a moderate level of stigma, which includes social discrimination, shame, and avoidance in social interactions. This stigma significantly affects the family's support for the patient. Most patients exhibit a moderate level of medication adherence. Family involvement plays a crucial role in improving medication adherence in patients with mental disorders. There is no significant relationship between family stigma and medication adherence in patients with mental disorders at the Langsa Barat Community Health Center.